Polietes Rondani 1866 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Polietes Rondani, 1866 Polietes Rondani, 1866: 91. Type-species: Musca lardaria Fabricius, 1781, by original designation. Polietes domitor (Harris, 1780) Musca domitor Harris, 1780: 148, plate 43 fig. 71. Type-locality: not stated (South-east England). Type-series lost (Pont & Michelsen, 1982: 33). Musca albolineata Fallén, 1823a: 54. Type-locality: Sweden, Skåne, Äsperöd. Lectotype ♂, NHRS (designated by Pont, 1984b: 280). Siberian records: Urals (Zimin & El’berg, 1970: 587); Urals, Zlatoust (Stein, 1916: 20); Yamalo-Nenezkiy AO: Labytnangi, Muzhi (Gagarin & Veselkin, 1987: 215); Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 232); Kurganskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 226); Respublika Altay (Sorokina, 2006b: 139); Yakutskaya Oblast’ (Hennig, 1963c: 911); North Respublika Sakha [Yakutiya]: Verchoyansk, Bagatay (Sychevskaya, 1972: 150); West and East Siberia (Pont, 1986a: 86). General distribution: Palaearctic Region, from Europe east to Japan. Polietes hirticrus Meade, 1887 Polietes hirticrus Meade, 1887: 179. Type-locality: United Kingdom, England, North Yorkshire, Bolton Abbey. Holotype ♂, BMNH (Pont, 1984a: 12). Siberian records: North Respublika Sakha [Yakutiya]: Verchoyansk, Bagatay (Sychevskaya, 1972: 150, 152); West and East Siberia (Pont, 1986a: 86). General distribution: Holarctic Region; in the Palaearctic, from the United Kingdom, Russia (West and East Siberia), Mongolia and China. Polietes lardarius (Fabricius, 1781) Musca lardaria Fabricius, 1781: 436. Type-locality: Germany. Holotype / syntypes,?sex, destroyed, formerly in ZMUC, Fabricius collection (Michelsen, 1979: 185). Siberian records: Urals (Hennig, 1963d: 913); Novosibirskaya Oblast’ (Sorokina, 2006a: 226); near Biysk and Altay Mts (Sychevskaya, 1978: 83); Respublika Altay (Sorokina, 2006b: 139); valley of River Yenisey, taiga: Krasnoyarsk, Yeniseysk (Sychevskaya, 1974: 130); West and East Siberia (Pont, 1986a: 86). General distribution: Palaearctic Region, from Europe ...